Challenges and Adaptation Strategies of Pre-Service EFL Teachers: An International Short-Term Teaching Program in Thailand - Asfihana, Raida; Putri, Nabil Adhalia (Universitas Sulawesi Barat, 2025)
In a short-term international teaching program in Thailand, pre-service English teachers' barriers and adaptation techniques were examined. A qualitative narrative technique and in-depth interviews with nine pre-service English teachers were used in the study to identify a number of significant issues. Large class sizes and language barriers were some of these issues that made teaching more challenging. Pre-service English teachers employed a variety of strategies to overcome these obstacles. Multimedia tools and visual aids were widely used to bridge language gaps and make complex concepts easier to understand. Teachers fostered collaborative learning environments, encouraging students to collaborate, share ideas, and support one another during the learning process. The results emphasized the crucial role of pre-program planning and cultural competency in overcoming challenges in foreign teaching environments. Well-prepared teachers were better able to adjust their teaching strategies and establish rapport with their students. The importance of adaptable teaching strategies, which allow teachers to adjust to varying classroom dynamics, was also highlighted by the study. By emphasizing the flexible teaching methods in cross-cultural settings, this research contributed to the development of successful teaching strategies and international education program designs. It provided valuable insights on how to better prepare teachers for overseas programs and enhance the teaching and learning process overall.